Pembangkangan Mistik Jawa Dalam Suluk Cebolek (Episode Haji Ahmad Mutamakin) - Muzairi, Muzairi (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2011)
Haji Ahmad Mutamakin lived during the time of Sunan Mangkurat IV (1719-26 A.D.) and of his son Paku Buwana II (1726-49 A.D.) in the village of Cabolek in the Tuban district, on the northern coast of East Java. He preached the Science of Reality (Ilmu Hakekat) to many. He disregarded the revealed Law (Shari’a). His behavior constituted a scandal to Muslims throughout the Tuban area. He was regarded by many as an enemy not only because he had infringed the Law of the Prophet but also because he was considered to have been to the king.